Growth of titanium dioxide nanorod arrays through the aqueous chemical route under a novel and facile low-cost method - Mohd. Yusoff, Marmeezee; Mamat, M.H.; Malek, Mohd Firdaus; Abu Bakar, Suriani; Mohamed, Azmi; Ahmad, Mohd Khairul; Alrokayan, Salman A.H.; Khan, Haseeb Ahmad; Rusop, Mohamad (Elsevier, 2016)
Titanium dioxide (TiO2) nanorod arrays were successfully synthesized through a facile aqueous chemical route on a fluorine tin oxide-coated glass substrate in a Schott bottle with cap clamps. Distinct rutile phase TiO2 peaks were observed via X-ray diffraction and micro-Raman spectroscopy. The surface morphology depicted in field-emission scanning electron microscopy and atomic force microscopy images showed that the nanorod arrays were successfully synthesized on the substrate. Moreover, these arrays possessed an average diameter of 120 nm and an average length of 1.52 mm. The prepared TiO2 nanorod arrays exhibited high absorbance properties in the ultraviolet (UV) region (o400 nm). In this study, the synthesized arrays may be applied in optical sensing based on the steady photocurrent results obtained under UV irradiation in a sodium sulfate electrolyte solution.